Analysis of the Influence of Traffic Performance on Air Quality (Case Study: Menteng Raya Bintaro Road Section) - Isradi, Muhammad; Novianty, Nadira; Dermawan, Widodo Budi; Rifai, Andri Irfan (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
Menteng Raya Bintaro Road Section as one of the main corridors experiences similar problems with increased air pollution and noise due to transportation activities. This study aims to analyze traffic operational performance and examine the relationship between vehicle density and air quality (PM2.5) and noise level on Menteng Raya Bintaro Road Section. The research method uses a traffic performance analysis approach based on the 2023 Indonesian Road Capacity Guidelines (PKJI), with data collection through direct observation for three day) using a time interval of 15 minutes. Measurements include vehicle volume, PM2.5 concentration, and noise levels during peak traffic hours. The results of the study show that traffic performance on Menteng Raya Bintaro Road Section is still in normal condition with the highest volume of 3,036 vehicles/hour (Tuesday afternoon 17:15–18:15), degree of saturation (DJ) 0.57 (below the threshold of 0.85), and road capacity of 5,372.97 Vcu/Hour. However, environmental quality showed unhealthy conditions with the highest PM2.5 concentration reaching 91.67 μg/m³ (exceeding the 55 μg/m³ quality standard) on Tuesday and the highest noise level of 88.33 dB(A) (exceeding the 55 dB(A) quality standard for residential areas). Correlation analysis revealed a strong positive relationship between traffic density and PM2.5 concentrations, particularly on weekdays with values of R² = 0.6143 (Tuesday) and R² = 0.5843 (Thursday), suggesting 58-61% of air quality variations were explained by traffic activity. A similar relationship was identified at the highest correlation noise level on Tuesday (R² = 0.5113).